Handbuch Sprache und Wissen - Felder, Ekkehard; Gardt, Andreas (Handbücher Sprachwissen, 2015)
The inaugural volume of the Handbücher Sprachwissen series demonstrates the relevance of language as a symbolic system for creating knowledge and applying it in social domains and other spheres of activity (medicine, law, business, etc.). The series takes a language-systemic perspective that goes from sound to text and discourse, combining it with a usage-oriented approach focusing on linguistic phenomena as such. -- Publisher description
Hier auch später erschienene unveränderte Nachdrucke
Literaturangaben
Keywords: Aufsatzsammlung; Sprache; Wissen; Fachsprache; Sprachgebrauch; Sprachvariante